Life through saved papers: building memories and historical narratives through personal collections - dos Santos, Rodrigo Luis (2018)
In this article we aim to establish some reflections about the construction of memories, through the personal collections. We base our analysis on the perception that the constitution of collections constitutes a framework of memory, a resource used by individuals to leave an image of themselves for the social environment in which they were inserted. To do so, we will adopt as laboratory of analysis the personal collection of the political and intellectual Carlos de Souza Moraes, nowadays under the responsibility of the Historical Museum Visconde de São Leopoldo, in the municipality of São Leopoldo/RS.